The Modelling Capacity of Tapin River using HEC-RAS 5.0.7 Application : PEMODELAN KAPASITAS TAMPUNGAN SUNGAI TAPIN DENGAN APLIKASI HEC-RAS 5.0.7 - Dwi Surya Saputri; Noordiah Helda (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
Flooding is an event that occurs when water inundates dry land or when a river's flow exceeds its capacity. According to the National Disaster Management Agency (BNPB), in 2021, flooding occurred in Tapin, triggered by heavy rainfall. To analyze the river’s capacity to handle floods, it is necessary to use hydraulic modeling through the HEC-RAS application, which provides insight into the river's ability to accommodate floods, particularly after the construction of the Tapin Dam. This study aims to analyze the flood discharge volume based on hydraulic analysis using HEC-RAS 5.0.7. The study uses secondary data, including Digital Elevation Model (DEM) data, Global Precipitation Measurement (GPM) satellite rainfall data, and Cross Section data. The method used for the calculation analysis is the Nakayasu Synthetic Unit Hydrograph method. Based on the hydraulic analysis results, the maximum flood discharge before the Tapin Dam construction, for return periods ranging from 2 to 100 years, is between 202.07 m³/s and 520.13 m³/s. Meanwhile, after the construction of the Tapin Dam, the maximum flood discharge for the same return periods is between 147.15 m³/s and 316.69 m³/s.